Kemampuan Membedakan Antara Kosakata Baku Dengan Kosakata Tidak Baku Dalam Karangan Bahasa Indonesia Siswa Kelas V SD Negeri 59 Noling Kabupaten Luwu - Diska Muna Mandika; Tarman A. Arif; Hambali Hambali (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The study aims to describe the level of students' ability to distinguish between standard and non-standard vocabulary in the Indonesian language. The population in this study was a student of V grade SD State 59 Noling who totalled 35 people. Data collection is done through test techniques, while data analysis is done using percentage techniques. This is evident from the data analysis that showed that 77.1% of the students of the sample obtained a score of 6.5 above, whereas the students obtaining a score below 6.5 was 22.65%. On this basis, it is expected that the learning process in the classroom, the teacher intensively gives tasks or training to the students in particular in terms of the difference between standard and non-standard vocabulary so that in the end students can establish the distinction between the two.